Research of the Problems of Financial Support for the Development of Transport Infrastructure in Kharkiv Region - Bogdan, N; Pohasii, S; Krasnokutska, I (International Journal of Engineering and Technology, 2018)
The purpose of the article is revealing the problems of development of transport infrastructure of the region from the financial standpoint, analysing modern approaches to the development of transport infrastructure at the regional level and the financial aspects of its support.It was found that public entities and local authorities have difficulties in financing development of transport infrastructure by state structures and local self-government bodies without any support. It was determined that Kharkiv region is one of the regions with the most developed transport infrastructure, which comprises railways, auto transport, and aviation. The region has a developed system of public transportation. It was justified that in order to maintain and develop the infrastructure of Kharkiv region, the strategic directions of the development of the region should be defined and the plan should be developed to attract investment which will have positive influence on the economy of the region. A number of measures must be taken for solving the problems of the transport infrastructure in Kharkiv region, but these activities require investment in the transport industry that cause difficulties in recessionary environments.The set of targets for solving the problems of funding the development of transport infrastructure of Kharkiv region in the context of the Ukrainian National transport strategy for the period up to 2030 has been developed. The comparative description of sources of financing has been considered. As the results, the best option of financing the transport infrastructure has been selected as the combination of budget resources and other sources of funding (funds from international financial organisations, state guarantee loans, funds of investors, PPP). Detailed elaboration of such a mechanism should be the subject of further research in this area.Â Â